Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1029/2021ef002612
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rocket Launch and Space Debris Air Pollutant Emissions on Stratospheric Ozone and Global Climate

Abstract: The space industry is one of the world's fastest growing sectors. Global revenue generated from this industry is forecast to grow from 350 million USD in 2019 to more than 1 trillion USD by 2040 (Morgan Stanley, 2020). This demand stems from significantly reduced launch costs driven by commercialization (Jones, 2018), increased reliance on satellite technologies for global positioning systems, surveillance and broadband internet (Alvino et al., 2019;Dolgopolov et al., 2018;George, 2019), and postulated space r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
(89 reference statements)
0
39
0
3
Order By: Relevance
“…35 It has been reported that nearly 95% of the total amount of NOx released is due to re-entry, whereas nearly 78−79% of the total amount of H 2 O and black carbon and nearly 68−69% of the total amount of chlorine and Al 2 O 3 are emitted in the atmosphere from the process of launching rockets to space. 35 This is shown to have a direct negative effect on climate change due to global warming and ozone layer depletion. 44 Another study analyzed the atmospheric pollution in the stratosphere specifically, at which it was concluded that the pollutants emitted due to spacecraft incineration in the atmosphere results from the vaporization of the metals present in spacecraft components; these metal particles are believed to integrate with the meteoric dust naturally present in the various atmospheric layers.…”
Section: Cosmic and Space Pollutionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 It has been reported that nearly 95% of the total amount of NOx released is due to re-entry, whereas nearly 78−79% of the total amount of H 2 O and black carbon and nearly 68−69% of the total amount of chlorine and Al 2 O 3 are emitted in the atmosphere from the process of launching rockets to space. 35 This is shown to have a direct negative effect on climate change due to global warming and ozone layer depletion. 44 Another study analyzed the atmospheric pollution in the stratosphere specifically, at which it was concluded that the pollutants emitted due to spacecraft incineration in the atmosphere results from the vaporization of the metals present in spacecraft components; these metal particles are believed to integrate with the meteoric dust naturally present in the various atmospheric layers.…”
Section: Cosmic and Space Pollutionmentioning
confidence: 99%
“…45 Table 1 summarizes the main pollutants emitted along with their sources of emission, probable fates, and associated effects. Figure 1 below provides a visual mapping of these pollutants from previous studies 6,10,11,16,23,31,33,[35][36][37][38][41][42][43][44]53 while highlighting their trajectory and circulation path in depth.…”
Section: Cosmic and Space Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…High altitude cloud formation and their radio interference and potential mitigation solutions also remain open areas of research [4,24]. Furthermore, little research has been published on the environmental consequences of rocket disposal, including the melting of upper rocket stages as they reenter the atmosphere from space [39]. These metal particles may be warming or cooling the atmosphere and consequently a form of geoengineering with poorly understood global effects.…”
Section: Radiative Forcing and Climate Changementioning
confidence: 99%